A study of the impact of disease burden in quality of life of people with pre-End-Stage and End-Stage Renal Disease - Helen Georgiadou; Theodora Kafkia; Eugenia Minasidou; Kyriakos Kazakos; Alexandra Dimitriadou (Ene, 2017)
Introduction: Diabetes Mellitus (DM) is a common chronic disease accompanied by severe complications. It is the leading cause of End-Stage Renal Disease (ESRD) requiring management either by haemodialysis (HD) or peritoneal dialysis (PD). The chronicity of the disease, and its complications, affects the psychological, family and social life of the patients and their Quality of Life (QoL). Aim: of the present study was to estimate the disease burden of patients with diabetic nephropathy (DN) during pre-ESRD and during End-Stage Renal Disease. Methods: A sample of 103 patients with DN treated at the General Hospital of Veria were studied during May and June 2016. The study was conducted using the Dialysis Symptoms Index (DSI) for the assessment of Chronic Kidney Disease (CKD) symptom load and the European Quality of Life (EuroQol) questionnaire for assessing the QoL of patients in the Renal Outpatient Clinic, Haemodialysis and Peritoneal Dialysis Unit. Results: It was found that the Renal Replacement Method (HD or PD), the presence of DM and CKD's stage affect significantly the patients' self-assessment regarding painful symptoms of DN. Furthermore, the above factors have major impact on some aspects of patients' QoL, such as mobility and self-care. Conclusions: Pre-End Stage patients experience more severe painful symptoms of DN compared to patients on Renal Replacement Therapies.